Preliminary experience on subcutaneous venous access device (chemoport) in a teaching hospital in Kathmandu - Joshi, Robin (Journal of Kathmandu Medical College, 2016)
Background: Modern subcutaneous venous access device or chemo port nowadays is a vital device used in case of chronic diseases. It is now an established device for administration of medication and blood withdrawal without difficulty and negating repeated skin punctures for those patients who need repeated and long term intravenous medication. But, these devices are not without complications.Objective: To assess preliminary technical success and complication rates of the ultrasound and fluoroscopy guided placement of subcutaneous venous access device.Methods: Between November 2012 to May 2015, 10 port catheter components were implanted. All components were inserted under image guidance. Ultrasound guided puncture of right internal jugular vein was preferred and position of tip of catheter was confirmed by fluoroscopy. Early and late complications were evaluated. The overall cost of the chemo port was also taken into consideration.Results: The implantation was inserted in ten cases. Four patients had ovarian carcinoma, three patients metastatic colonic carcinoma, one had testicular cancer with meditational mass, one patient had metastatic invasive urinary bladder carcinoma and another one had porphyries whose peripheral venous access were all thromboses due to repeated puncture. Peri-procedural early complications like blockage, thrombosis, leak were not observed, however one patient had catheter related fever. Late complications like blockage, port, fractures, dislodgement, venous thrombosis were also not found but One patient had port pocket infection. The cost of the port device in all cases was about 50,000 Nepalese rupees.Conclusion: Larger number of case is required for better statistical evaluation. The main reason for the refusal of subcutaneous venous access device insertion by the patients was the high cost of the device. Cather-related morbidity was in acceptable range so chemo port insertion is feasible in Nepal. Major life threatening complication was not observed.Journal of Kathmandu Medical College, Vol. 4, No. 2, Issue 12, Apr.-Jun., 2015